Potential Applications of Ferrocene as a Structural Feature in Antioxidants - Liu, Zai-Qun (Mini Reviews in Medicinal Chemistry, 2011)
Comparing with the wide usage of ferrocene in novel materials, ferrocene was unusually applied to be a structural feature in designing drugs even though some researchers pointed out that ferrocene and its derivatives possessed potential pharmacological applications. This was due to that low polarity limited bioavailability of ferrocene in vivo. Since ferrocene was inert to the oxidation at atmosphere, it was deduced that synthetic derivatives of ferrocene may be a novel kind of antioxidant, in which other organic groups may enhance the bioavailability of ferrocene, or large conjugated system formed among ferrocenyl and other organic groups may increase the antioxidant effectiveness. Thus, synthetic derivatives of ferrocene were divided into nonconjugated and conjugated ones in this review. For nonconjugated ferrocenyl derivatives, carbon chain or simple group attached one or two cyclopentadienyl rings in ferrocene to form a novel molecule with ferrocenyl group. The aim of synthesis of nonconjugated ferrocenyl compounds was to increase the bioavailability of ferrocene in vivo. On the other hand, the conjugated ferrocenyl derivatives referred to introduce other group to form a conjugated system with the cyclopentadienyl ring in ferrocene. The large conjugated system was beneficial for the single electron to dispense among the whole molecule while forming radicals, and enhanced the antioxidant capacity of the whole molecule. This review summarized the potential usage of ferrocene in antioxidants.
Keywords: inert